A comparison of the reactivating and therapeutic efficacy of two novel bispyridinium oximes (K727, K733) with the oxime HI-6 and obidoxime in sarin-poisoned rats and mice. (20th April 2015) - Kassa, Jiri; Sepsova, Vendula; Matouskova, Lenka; Horova, Anna; Musilek, Kamil
Abstract: The ability of two novel bispyridinium oximes K727 and K733 and currently available oximes (HI-6, obidoxime) to reactivate sarin-inhibited acetylcholinesterase and to reduce acute toxicity of sarin was evaluated. To investigate the reactivating efficacy of the oximes, the rats were administered intramuscularly with atropine and oximes in equitoxic doses corresponding to 5% of their LD50 values at 1 min after the intramuscular administration of sarin at a dose of 24 µg/kg (LD50 ). The activity of acetylcholinesterase was measured at 60 min after sarin poisoning. The LD50 value of sarin in non-treated and treated mice was assessed using probit-logarithmical analysis of death occurring within 24 h after intramuscular administration of sarin at five different doses. In vivo determined percentage of reactivation of sarin-inhibited rat blood, diaphragm and brain acetylcholinesterase showed that the potency of both novel oximes K727 and K733 to reactivate sarin-inhibited acetylcholinesterase roughly corresponds to the reactivating efficacy of obidoxime. On the other hand, the oxime HI-6 was found to be the most efficient reactivator of sarin-inhibited acetylcholinesterase. While the oxime HI-6 was able to reduce the acute toxicity of sarin >3 times, both novel oximes and obidoxime decreased the acute toxicity of sarin <2 times. Based on the results, we can conclude that the reactivating and therapeutic efficacy of both novel oximes K727 and K733 is significantly lower compared to the oxime HI-6 and, therefore, they are not suitable for the replacement of the oxime HI-6 for the antidotal treatment of acute sarin poisoning.